Charting secrets : trade like a machine and finally beat the markets using these bulletproof strategies - Bedford, Louise (Wrightbooks, 2013)
A leading Australian trader shows you how to succeed on the sharemarket with proven charting techniques Now completely revised with the latest trading information, this revised edition of bestselling author Louise Bedford's Charting Secrets is the perfect guide for beginners and experienced traders and chartists alike. Unlike other books on trading, you'll find no get-rich-quick schemes here. Bedford believes that successful trading is a matter of study and hard work, just like any other job. With this in mind, Charting Secrets serves as a workbook that will have you pra.